Ensino por modelação de discriminações condicionais envolvendo diferentes estruturas de treino e formaçao de classes equivalentes. - Tini, Juliana Rodrigues (Universidade Federal de São Carlos, 2004)
The purpose of this study was to analyze observational learning of conditional discriminations and equivalence class formation, in six mentally retarded participants, involving the training structures Linear, CaN and SaN. In general, the reported studies have submitted each participant s group to a different training structure. Then, they have compared inter group performance. In the present study, the dependent variable participant was controlled: the same participant was submitted simultaneously to the three training structures. Conditional discriminations among three classes of object pictures, with three stimuli each, were taught through modeling. Each class was taught through a different training structure, A1B1/ B1C1 representing the Linear structure, A2B2/ C2B2 the CaN structure and e B3A3/ B3C3 the SaN. Teaching through modeling consisted in the participant s observation of a demonstrator (experimenter) performing correctly matching to sample trials. After each demonstration trial, the participant was exposed to an identical trial that differed from the one just demonstrated only in the comparison stimuli s position. Subsequently, a new demonstration trial was presented and followed by another trial, without demonstration, presented to the participant. This sequence was followed until the end of the session. A1B1, A2B2, B3A3 were the first taught relations. After reaching the individual tests criterion of these relations, B1C1, C2B2 and B3C3 were taught through modeling. After the criterion to these relations was reached, the participant performed a session containing all trained relations. In case the participant reached criterion, he proceeded through a session of transitivity and equivalence class test (AC and CA). All six participants reached criterion of conditional discrimination learning through observation. For three participants, an additional training procedure was required. One participant established equivalence class, while the others showed consistent relations to other classes and/or inconsistent relations. Regarding the three training structures: the results obtained by five of the six participants did not show differences, what suggests that this variable has relatively little importance, at least in experimental designs like the one presented here. The present study showed that it is possible to teach conditional discrimination through modeling to mentally retarded people. It also indicates that implementing equivalence procedures that use teaching through modeling may have prospective educational implications to children with developmental disabilities. However, it is still needed to discuss possibilities for these individuals to establish equivalence classes. These possibilities are related to the difficulties found in the direct manipulation of the contingencies present in conditional discrimination teaching through modeling, including measuring the participant s performance during the training phases. These difficulties open avenue for future investigations.
Keywords: Educação especial; Equivalência de estímulos; Ensino por modelação; Estrutura de treino; Teaching through modeling; Learning through observation; Training structure; Stimulus equivalence; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL